2022
DOI: 10.1007/s10657-022-09741-w
|View full text |Cite
|
Sign up to set email alerts
|

On Coase and COVID-19

Abstract: From an epidemiological perspective, the COVID-19 pandemic is a public health crisis. From an economic perspective, it is an externality and a social cost. Strikingly, almost all economic policy to address the infection externality has been formulated within a Pigovian analysis of implicit taxes and subsidies directed by a social planner drawing on social cost-benefit analysis. In this paper we examine the alternative economic methodology of the externality. We seek to understand how an exchange-focused and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Transaction costs refer to the costs of negotiating, signing, and fulfilling a contract. In addition, Coase believes that the transaction structure should include contracts and can also equate contract issues with organizational system issues so that transaction costs can be explained from the perspective of contracts [24][25][26]. Based on Coase's point of view, Williamson proposed that transaction costs can be divided into two categories: "ex ante" and "ex post", according to contract standards.…”
Section: Theoretical Framework Constructionmentioning
confidence: 99%
“…Transaction costs refer to the costs of negotiating, signing, and fulfilling a contract. In addition, Coase believes that the transaction structure should include contracts and can also equate contract issues with organizational system issues so that transaction costs can be explained from the perspective of contracts [24][25][26]. Based on Coase's point of view, Williamson proposed that transaction costs can be divided into two categories: "ex ante" and "ex post", according to contract standards.…”
Section: Theoretical Framework Constructionmentioning
confidence: 99%
“…The scope of discussion of this research is that local government revenue includes original regional income and transfer income after the establishment of the Covid-19 pandemic, namely April to December 2021 with comparative data on regional original income for the period April to December 2020. However, Ronald Coase argues that this is not the only solution to overcome social costs because there is a failure to symmetrically recognize each externality situation, thus failing to focus on maximizing economic efficiency [8]. The most important thing is that transaction costs are low and property rights are clear.…”
Section: The Scope Of Researchmentioning
confidence: 99%
“…The most important thing is that transaction costs are low and property rights are clear. Coase explains that parties can bargain in an efficient and appropriate way to overcome these externality problems [8]. One of the Coasian solutions that can be provided is to provide subsidies, including health equipment that is very necessary for the community during the COVID-19 pandemic can be provided with subsidies so that the prices sold to the public are cheaper and more affordable.…”
Section: The Scope Of Researchmentioning
confidence: 99%
“…Addressing the problems presented by the COVID-19 pandemic, researchers in liberal political economy have challenged the supposed trade-off between protection against infectious disease and economic freedom (Furton, 2023 ; Geloso et al, 2021 ; Geloso & Murtazashvili, 2021 ; Koyama, 2023 ), shown that political incentives encourage officials to adopt stricter measures than is economically efficient (Allen, 2022 ; Boettke & Powell, 2021 ; Hebert & Curry, 2022 ; Leeson & Thompson, 2023 ; Murtazashvili and Zhou this volume ; cf. Garzarelli et al, 2022 ), including measures that persist after the danger has passed (Goodman et al, 2021 ), proposed that spontaneous endogenous citizen responses to novel infections are more effective than typically predicted (Allen et al, 2022 ; Leeson & Rouanet, 2021 ), and highlighted how decisions in the private sector can internalise many of the relevant externalities associated with the infection (Albrecht & Rajagopalan, 2023 ). Paniagua and Rayamajhee challenge the presumption that the global scale of the pandemic means that national and international policy intervention are where any possible solution lies (Paniagua & Rayamajhee, 2022 ; Rayamajhee and Paniagua 2022 ).…”
Section: Introductionmentioning
confidence: 99%